Failure rates of miniscrews inserted in the maxillary tuberosity - Azeem,Muhammad (2019)
ABSTRACT Introduction: Anchorage conservation in orthodontics has always been a challenge. Objective: The aim of this current study was to find out the failure rate of miniscrews inserted in the maxillary tuberosity (MT) region. Methods: This pilot study consisted of 40 patients (23 female, 17 male; mean age = 20.1±8.9 years) that had received 60 MT miniscrews for orthodontic treatment. Clinical notes and pictures were used to find out the primary outcome of miniscrew failure. Independent failure factors were also investigated. Logistic regression analysis was done for predictor’s relation with MT miniscrews failure. Results: There was no significant correlation in failure rate according to various predictor variables, except for miniscrews installed by lesser experienced operators, which showed significantly more failure. The odds ratio for miniscrew failure placed by inexperienced operators was 4.16. Conclusion: A 26.3% failure rate of mini-implants inserted in the MT region was observed.